Eastern Europe in the Middle Ages (500-1300) - Curta, Florin, author.
1 online resource.
Keywords: This book provides a comprehensive synthesis of scholarship on Eastern Europe in the Middle Ages. The goal is to offer an overview of the current state of research and a basic route map for navigating an abundant historiography available in more than 10 different languages. The literature published in English on the medieval history of Eastern Europe—books, chapters, and articles—represents a little more than 11 percent of the historiography. The companion is therefore meant to provide an orientation into the existing literature that may not be available because of linguistic barriers and, in addition, an introductory bibliography in English.